Child Care and Work Challenges for Maine’s Parents of Children with Special Needs - Ward, Helen; Atkins, Julie; Oldham, Erin (Maine Policy Review, 2009)
Research by the authors with parents, child care providers, and other service providers found that parents of children with special needs face particular challenges trying to maintain stable employment while balancing work and family. These parents have more difficulty finding and keeping child care for children with special needs, and there is a lack of coordination of therapy with child care programs. Since the study was completed, Maine has taken several steps to begin to address these issues
Keywords: Maine; childcare; special needs children